Assessment of diet of young medium- and long-distance runners - Tota, L.; Pilch, W.; Hodur, M.; Sagalara, A. (Medicina Sportiva, 2013)
Nutrition is one of the main factors influencing physical performance. Furthermore, a well-balanced diet is a key determinant of optimal biological development of young athletes. Objective: To assess the diet of young medium- and long-distance runners. Methods: An assessment of the diet of 45 athletes (20 adolescent females and 25 adolescent males) specializing in medium- and long-distance running in the junior and young junior categories was performed by examining dietary records for 6 consecutive days. The study was conducted in October 2010, towards the end of the low-intensity stage of the yearly training cycle. Calculations were performed using the Wikt-1 software. Obtained data were compared to norms for adolescent males and adolescent females engaging in rigorous physical activity. Results: The daily caloric intake for the athletes participating in this research amounted to 3569 kcal for the males and 2654 kcal for the females - considerably lower than the norms proposed for this age group, i.e., 3900 kcal for adolescent males and 2900 kcal for adolescent females. Daily intake of protein and carbohydrates was lower than the recommended norm, while the daily intake of fats was slightly higher than the norm. Intake of energy with food was insufficient compared to the norms. When compared to the norm, an analysis of the daily intake of nutrients in the study`s participants found insufficient amounts of Na, K, Ca, F, Mg and Fe, as well as vitamins B1, B2, PP, C, and D. Conclusions: These results indicated that the diet of the athletes participating in this research did not meet the norms recommended by nutritional experts. A lack of appropriate balance in the daily nutrition in study participants meant that their intake of energy was too low to meet the energy expenditure stemming from daily training and participation in sports competitions.